School sanitation and hygiene education indicators - Marielle Snel; Kathleen Shordt; Sascha de Graaf (2003)
This paper starts off with a focus on monitoring within the context of SSHE. This is followed with a section on monitoring indicators. Finally, some concluding remarks are given regarding the role of monitoring in SSHE projects.